Parent perspectives on childhood vaccination: How to deal with vaccine hesitancy and refusal? - Bianco, Aida; Mascaro, Valentina; Zucco, Rossella; Pavia, Maria (Vaccine, 2019)
The aims of the study are to evaluate attitudes about childhood vaccines and vaccine refusal or delay among parents and to assess the role played by the variables mapped as potential determinants to suggest strategies that could improve childhood vaccination rates. The cross-sectional study was intended for parents of kindergarteners. Parental attitudes were measured using the Parent Attitudes about Childhood Vaccines (PACV) survey, to screen for Vaccine Hesitancy (VH). In addition, selected factors have been grouped in three categories (contextual, individual and group and vaccine/vaccination-specific influences), and were explored as potential determinant of VH and vaccination refusal or delay. 7.7% of subjects were defined as VH parents (VHPs) through PACV score, while 24.6% reported having refused or delayed at least one dose of vaccine for their child. VH was more common in those parents that decided not to vaccinate their child after having received information from mass-media, in those who did not agree with mandatory vaccinations, and in those who agreed with political leaders who oppose to vaccination. Vaccine refusing/delaying parents were more frequently those who agreed that infant vaccinations are primarily an economic business of pharmaceutical companies, and who disagreed that access to the kindergarten should only be allowed to children who had been vaccinated. The findings of the present study emphasize the importance of PACV as a tool to screen VHPs. Furthermore, results highlight important potential determinants of VH, such as communication and media environment, and attitudes about prevention. Health care providers could act as key components to improve the public trust to scientific and epidemiological evidence.